Pengaruh Konten Instagram @petualanganmenujusesuatu Terhadap Sikap Dalam Menjaga Kesehatan mental - Puspitasari, Septiana; Utomo, Ichsan Widi; Emeilia, Rindana Intan (CV. ITTC INDONESIA, 2023)
Mental health is a state in which a person experiences disturbances in thinking, feeling, and acting, although in milder levels compared to mental disorders. This can happen temporarily or as a reaction to the stresses of life. @petualanganmenujusesuatu is one of the Instagram accounts that actively disseminates information, knowledge and support to increase awareness of its followers to pay more attention and maintain mental health through uploaded Instagram content. The purpose of this study is to determine whether there is an influence of Instagram content @petualanganmenujusesuatu on attitudes in maintaining mental health. The theory underlying this research is the stimulus-organism-response (SOR) theory in which the communication stimulus received by the individual has the potential to influence the response. The effects caused can be interrelated with the message delivered and the response received by the recipient of the message. This study used descriptive quantitative methods with data collection techniques using questionnaires. The results of this study show that there is a significant influence of Instagram content @petualanganmenujusesuatu on followers' attitudes in maintaining mental health. This finding supports the hypothesis that the calculated t value of 8.666 > t table 1.984 Ho is rejected, and Ha is accepted.